Conceptual visions of standard capital measurement Measures and determinants of disclosure to create Sustainable competition In light of the knowledge economy (Journal of Accounting and Financial Studies ( JAFS ), 2018)
This century is witnessing changes in various fields,which have become a challenge to the enterprises in the contemporary business environment, the most important of which is the importance of measurement and disclosure of the role of knowledge capital in the transition to the knowledge economy, which is no longer the land and labor and physical capital resources the basic. Knowledge-based capital has emerged that provides the enterprise with an area of ​​excellence and enhances its position to achieve competitive advantage. The research tackled the concept, objectives, components and importance of knowledge capital, which is fundamental in knowledge management, creating value added and enhancing competitiveness, as well as analyzing the different ways and means of measuring the cognitive head, the objective of the research is to explore the determinants affecting the level of accounting disclosure for knowledge capital. In the light of the results, a set of recommendations was reached to enable the business to raise awareness of the disclosure of the elements of knowledge capital and the need to adopt them as they have a positive role in improving the level of disclosure and the need to issue an accounting standard for knowledge capital to regulate its accounting treatment and disclosure limits In the financial statements in a way that does not contradict the accepted accounting principles.